Performance analysis and science mapping of institutional entrepreneurship research - Victor Tiberius; Meike Rietz; Ricarda B. Bouncken (Administrative Sciences, 2020)
Institutional entrepreneurship comprises the activities of agents who disrupt existing social institutions or create new ones, often to enable diffusion, especially of radical innovations, in a market. The increased interest in institutional entrepreneurship has produced a large number of scholarly publications, especially in the last five years. As a consequence, the literature landscape is somewhat complex and scattered. We aim to compile a quantitative overview of the field within business and management research by conducting bibliometric performance analyses and science mappings. We identified the most productive and influential journals, authors, and articles with the highest impact. We found that institutional entrepreneurship has stronger ties to organization studies than to entrepreneurship research. Additionally, a large body of literature at the intersection of institutions and entrepreneurship does not refer to institutional entrepreneurship theory. The science mappings revealed a distinction between theoretical and conceptual research on one hand and applied and empirical research on the other hand. Research clusters reflect the structure-agency problem by focusing on the change agent's goals and interests, strategies, and specific implementation mechanisms, as well as the relevance of public agents for existing institutions, and a more abstract process rather than agency view.
Keywords: 350; bibliometric analysis; business; co-citation analysis; co-occurrence analysis; entrepreneurship; institutional change; institutional entrepreneurship; management; science mapping